Marx e o labirinto da utopia - Viana, Francisco Antonio Marques (2010)
In Marx the thread of becoming is the praxis of human emancipation by means of Socialism and Communism. A universal construction, intrinsic to the break with Capitalism, the argumentation makes itself present in Marx s work during four decades. It involves, as a whole, the objective reality of the need of labor as merchandise and source of alienation, and of private property as the foundation of the estrangement brought about by the class society and by the predominance of the individual over the species. It comprehends all the forms of thought, starting with the social utopia, which reappears in the break of XIX century, with the reform of thought by adopting philosophy as the way for the anticipation of the future of human happiness. In Marx s argumentation, the bourgeois revolution of 1789 broke with Feudal society, but it did not abolish the exploration of man by man. It generated two antagonist and irreconcilable classes: the bourgeoisie and the proletariat. He argued that in the XIX century, the proletarian revolution emerged as the negation of negation, which, by the abolishment of private property it would inaugurate the real history of mankind. Utopist thought, which germinated with Saint-Simon, Charles Fourier and Robert Owen, considered becoming as the extension of the French Revolution, built by consciousness and the gradual reform of society. It denied the violent break with the actual society, thus affirming the concept of order. Instead of the proletariat revolution, it preached the union of classes, supported by good laws, good governments and the education for truth and goodness. The actual society was thus emptied to build, slowly, a new order. In both views of becoming, the center is man. The utopia in that context is no longer a no-where, as it was originally in the XVI century, in Thomas More s homonymous book. It becomes a geography of universal dimensions or, at least a European one, a knowledge and a possibility to overcome dialectically the bourgeois society. This was what Marx sought to bring about by uniting the philosophy of praxis with political economics and the revolutionary theory. This is what utopist thought tried to give form to by means of consciousness through convincing. The point of intersection is to be found in the primacy of the collective over the individual, stating the discarding of a civilization which consumed itself in its own contradictions so as to sow a society wherein thought and action were coincidental. A society where humanism weren t only a rhetorical tool, but the real of becoming, where man were a totality, and not a fragment, illusory representation of the real. A society wherein the end of the empire of necessity were the principle of the kingdom of liberty. These are horizons of construction which move through distinct routes - one through the revolutionary praxis, the organization of the proletariat; the other through consciousness, the good laws, education and the union of classes -, but which meet dialectically in the domains of the production of ideas, mobilization and the organization of the proletariat and of the society. They converge, especially, in the thought and action of anticipating the becoming of Socialism and Communism. Two routes, the same end?